Предисловие - Айбабин, А.И. (Материалы по археологии, истории и этнографии Таврии, 2000)
Настоящий выпуск подготовлен по материалам международной конференции «Византия и Крым», проводившейся в городе Севастополе 6-11 июня 1997 года. Ее организаторы (Крымское отделение Института востоковедения НАН Украины, Республиканский комитет по охране и использованию памятников истории и культуры и Национальный заповедник «Херсонес Таврический») приурочили конференцию к 175-летнего юбилею начала археологических раскопок Херсонеса - форпоста Византийской империи в Крыму. This volume is prepared on the materials of International Conference “Byzantium and Crimea” held in the city of Sebastopol in June 6-11,1997. The organizers (Crimean Branch of the Institute of Oriental Studies of NAN of Ukraine, republican Committee on Protection and Utilization of monuments of History and Culture and National Reserve “Chersonesos of Taurida”) was timed to coincide the Conference with the 175®* jubilee of the beginning of archaeological excavation in Chersonesos - the advanced post of the Byzantine Empire in the Crimea.